FOREIGN INVESTMENT REGULATION IN THE FIELD OF TOURISM ACCOMMODATION SERVICES IN BADUNG REGENCY - I Putu Harry Suandana Putra (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract The development of the tourism industry in Badung regency is interesting to foreign investors to invest in Badung regency, especially in the area of ​​tourism accommodation services. What are the local government authorities of Badung Regency in granting approval and permission of foreign investment in tourism accommodation? How is the regulation of foreign investment in tourism accommodation services in Badung regency? The type of research used in this study was normative legal research. The results showed (1) the authority of the local government of Badung regency related to the granting of foreign investment permit in the tourism accommodation can be seen from the provision of Article 19 of Badung Regulation No. 2 of 2012 which generally states that the local government of Badung regency is entitled to regulate tourism activities in the region; (2) The arrangement of foreign investment in tourism accommodation services in Badung Regency has not been accommodated in a more specific way through the regulation of Badung Regency. The absence of the specification of this rule would also affect the legal security and legal protection for foreign investors for their investment in tourism accommodation in the area. Keywords: accommodation, tourism, foreign investor, Badung